Responsible growth for the new millennium : integrating society, ecology and the economy - World Bank. (Washington, D.C. : World Bank, 2004)
This volume offers a vision of the mid-twenty first century that highlights the challenges that the international community will face in achieving balanced, equitable, and sustainable growth.
Includes bibliographical references and index.
ii 24/01/2019
Loans
Keywords: Economic development; Economic development--Environmental aspects; Natural resources--Management; Sustainable development; Economic development--Social aspects; Human ecology